Identification of novel MUNC13-4 mutations in familial haemophagocytic lymphohistiocytosis and functional analysis of MUNC13-4-deficient cytotoxic T lymphocytes. Issue 10 (1st October 2004) - Yamamoto, K; Ishii, E; Sako, M; Ohga, S; Furuno, K; Suzuki, N; Ueda, I; Imayoshi, M; Yamamoto, S; Morimoto, A; Takada, H; Hara, T; et al.
Abstract : Background: Familial haemophagocytic lymphohistiocytosis (FHL) has an autosomal recessive mode of inheritance and consists of at least three subtypes. FHL2 subtype with perforin ( PRF1 ) mutation accounts for 30% of all FHL cases, while FHL with MUNC13-4 mutation was recently identified and designated as FHL3 subtype. Objective: To examine MUNC13-4 mutations and the cytotoxic function of MUNC13-4 deficient T lymphocytes in Japanese FHL patients Methods: Mutations of MUNC13-4 and the cytotoxicity of MUNC13-4-deficient cytotoxic T lymphocytes (CTL) were analysed in 16 Japanese families with non-FHL2 subtype. Results: Five new mutations of the MUNC13-4 gene were identified in six families. The mutations were in the introns 4, 9, and 18, and exons 8 and 19. Two families had homozygous mutations, while the remaining four had compound heterozygous mutations. Cytotoxicity of MUNC13-4 deficient CTL was low compared with control CTL, but was still present. Clinically, the onset of disease tended to occur late; moreover, natural killer cell activity was not deficient in some FHL3 patients. Conclusions: MUNC13-4 mutations play a role in the development of FHL3 through a defective cytotoxic pathway.